Self- Induced Medical Abortion: An Emerging Issue of Safety and Access - Bajracharya, Manish; Tuladhar, Heera; Dwa, Yam; Bhandari, Sunita; Maharjan, Menu; Maskey, Smrity; Thakur, Minaxi (Journal of KIST Medical College, 2020)
Introduction: Access to safe abortion services has been the need of the current era. Medical abortion (MA) is a simple, safe and effective method of induced abortion. MA drugs have been approved by Government of Nepal for termination of pregnancy up to 63 days of gestation in safe abortion service sites. But registered as well as unregistered MA drugs have been widely and easily available without prescription even in rural settings. This has led to a tremendous increase in self-induced medical abortions and its adverse consequences. Aim of our study was to find out incidence of abortion related admissions and description of self- induced MA presented to our institution. Methods: Descriptive study was conducted in Department of Obstetrics and Gynecology of KIST Medical College Teaching Hospital (KISTMCTH) from January 2015 to December 2016. Cases of complications of self-induced medical abortions were studied in detail which included age, parity, gestational age, address, type of complications and management. Results: Total number of Gynecology related admission over the period was 308. Among these, abortion related admission were 95 (30.84%). 44(46.3%) were spontaneous abortion and 51(53.7%) were induced abortion. 22(43.1%) were admitted due to complications of self- induced MA like incomplete abortion, bleeding, shock, sepsis and renal failure. Most of the patients were of age group 20-25 years and were multigravida and had done MA in first or second trimester. Conclusion: Self-induced medical abortion is still practiced even in urban area, landing to tertiary care hospital with complications. Thus MA should be provided by registered medical practitioner.